The Role of Banking Services in Increasing the Efficiency of Economic Relations - Isomiddinovich, Asrorov Azizbek; oʻg‘li, Sayfiev Asror Erali; qizi, Umurzoqova Sevinch Karim (Journal of Innovation in Education and Social Research, 2024)
Commercial banks of Uzbekistan have become visible, first of all, as specialized credit institutions. This has gained urgent importance due to the fact that, on the one hand, it attracts temporarily free funds of farms, and on the other hand, it meets the financial needs of enterprises, private entrepreneurs and the population at the expense of the attracted funds.